Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor Treatment Response in Advanced Lung Adenocarcinomas with G719X/L861Q/S768I Mutations. Issue 5 (May 2015) - Chiu, Chao-Hua; Yang, Cheng-Ta; Shih, Jin-Yuan; Huang, Ming-Shyan; Su, Wu-Chou; Lai, Ruay-Sheng; Wang, Chin-Chou; Hsiao, Shih-Hsin; Lin, Yu-Ching; Ho, Ching-Liang; Hsia, Te-Chun; Wu, Ming-Fang; et al.
Abstract : Background: Epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) is the standard therapy for advanced lung adenocarcinomas with common EGFR mutations. Preclinical studies have suggested that uncommon G719X, L861Q, and S768I mutations are also sensitive to EGFR-TKIs. However, the efficacy of EGFR-TKIs in patients with these uncommon mutations remains unclear. Methods: A nationwide survey was performed to collect data from gefitinib and erlotinib treatment outcomes of patients with stage IIIB/IV lung adenocarcinoma bearing EGFR G719X/L861Q/S768I mutations. The results were compared with those regarding patients with exon 19 deletions or L858R mutations. Results: One hundred and sixty-one patients with uncommon EGFR mutations were enrolled from 18 institutes throughout Taiwan. Mutations of G719X, L861Q, S768I, G719X + L861Q, and G719X + S768I were observed in 78, 57, 7, 9, and 10 patients, respectively. After receiving EGFR-TKI treatment, patients with uncommon mutations exhibited a significantly inferior tumor response rate (41.6% vs. 66.5%; p < 0.001) and progression-free survival (median, 7.7 vs. 11.4 months; p < 0.001) than patients with common mutations. Among the patients who used EGFR-TKIs as first-line treatment, there was a significant difference in overall survival between these two groups of patients (median, 24.0 vs. 29.7 months; p = 0.005). Conclusion: Gefitinib and erlotinib are active in patients with G719X/L861Q/S768I mutations; however, less effective than in those with common mutations.